Features of the ethical-legal and institutional regulation of biotechnology in France, Italy, Germany and Austria - I V Ponkin; A A Ponkina (RUDN Journal of Law, 2014)
The article is one of a series of articles on the importance and characteristics of bioethics in the modern world and its interaction with the law. The article investigates the ethical-legal and institutional regulation of biotechnology in France, Italy, Germany and Austria. The authors studied the peculiarities of the legal and institutional regulation of clinical trials, in the field of embryology, in the field of stem cell technologies, including the use of stem cells, and in the field of genetic engineering, cloning in humans and animals, in the field of organ transplantation. The author's definition of bioethics (as science) and bioethics (as a system of regulatory statutes (lex biomedica), defining a set of ethical imperatives and approaches in medicine and health care, pharmaceutical and pharmacology).